2005
DOI: 10.1002/ejic.200500692
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure and Reactivity of Homo‐ and Heterobimetallic Complexes of the General Formula [Cp*Ru(μ‐Cl)3ML] [LM = (arene)Ru, Cp*Rh, Cp*Ir]

Abstract: The homo-and heterobimetallic complexes [Cp*Ru(µ-Cl)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Heterobinuclear complexes have long been investigated as catalysts, due to the potential for reactivity different from that of their mononuclear analogues. In such species, the two metals can work cooperatively or each can perform a different task which leads to an overall increase in activity. …”
Section: Introductionmentioning
confidence: 99%
“…Heterobinuclear complexes have long been investigated as catalysts, due to the potential for reactivity different from that of their mononuclear analogues. In such species, the two metals can work cooperatively or each can perform a different task which leads to an overall increase in activity. …”
Section: Introductionmentioning
confidence: 99%
“…As follows from the Cambridge Crystallographic Database, for the complexes [(C 5 R 5 )Ru(C 6 R 6 )] + (R = H, Alk) an analogous situation is observed. For example, the shortest Ru···arene and Ru···Cp* distances were observed in [(C 5 Me 5 )Ru(C 6 H 6 )] + (1.703 and 1.809 Å, respectively) and the longest in [(C 5 Me 5 )Ru(η 6 -5,6-dipropyl-2,3-dihydro-1 H -indene)] + (1.742 and 1.841 Å, respectively) …”
Section: Resultsmentioning
confidence: 99%
“…Selected parameters for these structures and for the previously described 13 3bPF 6 , 4bPF 6 , and 5bPF 6 are given in Table 1 (see also Table S1 in the Supporting Information for selected bond lengths and angles). 1.809 Å, respectively) 20 and the longest in [(C 5 Me 5 )Ru(η 6 -5,6dipropyl-2,3-dihydro-1H-indene)] + (1.742 and 1.841 Å, respectively). 21 Analysis of intermolecular contacts indicates that cations 4a are arranged in chains by weak π(C(sp 2 ))−π(C(sp 2 )) stacking interactions Cp(Co)•••Cp(Ir) (ca.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Severin et al reported that a mixed-ligand trichlorido-bridged diruthenium complex, [Cp*Ru­(μ-Cl) 3 Ru­( p -cymene)], is formed quantitatively upon mixing [Cp*RuCl] 4 and [( p -cymene)­RuCl 2 ] 2 . , On the basis of their observations, we succeeded in the exclusive preparation of a corresponding trihydrido-bridged diruthenium complex, [Cp ‡ Ru­(μ-H) 3 Ru­( p -cymene)] ( 2a ), using the 2-propanol/base method (Scheme a) . However, when [(C 6 H 6 )­RuCl 2 ] 2 was employed, a mixture of mixed-ligand di- and triruthenium complexes, [Cp ‡ Ru­(μ-H) 3 Ru­(C 6 H 6 )] ( 2b ) and [(Cp ‡ Ru) 2 {(C 6 H 6 )­Ru}­(μ-H) 4 (μ 3 -H)] ( 3b ), was obtained.…”
Section: Introductionmentioning
confidence: 87%